2000
DOI: 10.1136/bjo.84.8.903
|View full text |Cite
|
Sign up to set email alerts
|

Results of intraoperative mitomycin C application in dacryocystorhinostomy

Abstract: Aims-To evaluate the long term results of intraoperative mitomycin C application in dacryocystorhinostomy (DCR) surgery compared with results of the conventional procedure. Methods-In this prospective randomised controlled study, a total of 88 eyes diagnosed with acquired nasolacrimal duct obstruction were randomly divided into a conventional DCR group and a mitomycin C group in which mitomycin C was used during DCR surgery. The surgical procedures in both groups were exactly the same, except that in the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(71 citation statements)
references
References 20 publications
5
57
1
8
Order By: Relevance
“…Success rate of external DCR has been reported between 80-99% and average failure rate as reported in literature is 9.4%. [3][4][5][6][7][8]15,17,24 Failure is generally defined as having symptoms of excessive tearing with the inability to irrigate. Mc Pherson and Egelston noted that three out of seven patients in their study who underwent a second operation were found to have dense scar tissue present at the osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rate of external DCR has been reported between 80-99% and average failure rate as reported in literature is 9.4%. [3][4][5][6][7][8]15,17,24 Failure is generally defined as having symptoms of excessive tearing with the inability to irrigate. Mc Pherson and Egelston noted that three out of seven patients in their study who underwent a second operation were found to have dense scar tissue present at the osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Intraoperative application of Mitomycin C in DCR should prevent shrinkage of the final surface area of osteotomy, thereby inhibiting scarring around the common canaliculus opening and also prevent adhesion between osteotomy site and nasal septum. 15,17,18 A comparative study of conventional DCR and DCR with intra-operative MMC will clearly establish the efficacy of mitomycin c in improving the success rate in DCR. Hence, this prospective randomized study was undertaken to evaluate the role of mitomycin C in maintaining post-operative patency of nasolacrimal passage of DCR.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Liao et al used 0.2 mg/ml of MMC externally on the posterior flap and on the osteotomy site and removed after 30 min. 21 They reported 95.5% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…15, [20][21][22] Mitomycin-C, an alkaline agent is isolated from fermentation filtrate of 'Streptomyces caespitosus'. After intracellular enzyme reduction of the quinine and loss of methoxy, mitomycin-C becomes bifunctional or trifunctional alkylating agent.…”
Section: Discussionmentioning
confidence: 99%
“…Применяли данную методику и другие авторы, ис-пользуя концентрации митомицина-С от 0,2 мг/мл до 0,5 мг/мл [13,14], также вариабельным было время аппли-кации от 2 до 15 мин [15,16]. Период наблюдения за паци-ентами после операции также был различным и составлял от 6 до 12 мес [17,18].…”
unclassified